Measuring Compliance In Paying Agricultural Zakah: Case Study In Empat Lawang District, South Sumatra - Edo Ariansyah; Muhammad Rusdi; Abdullah Sahroni (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
This research uses a qualitative approach, the data in this research was obtained from primary data and secondary data. In collecting data using observation, interviews and documentation methods. Analysis of data obtained from interviews, field notes and other materials, arranged systematically so that it is easy to understand and explained in the form of quotations to determine the factors of farmer complance in agricultural zakat in Galang Village, Ulu Musi District, Empat Lawang Regency. The results of this research show that the factors that influence farmers' compliance in paying agricultural zakat are internal and external factors, internal factors consist of religiosity (lack of belief and obedience of farmers regarding agricultural zakat so that there is no encouragement from within farmers to pay agricultural zakat ), awareness (no self-awareness where farmers do not know about agricultural zakat), knowledge and education, and experience (farmers have no experience either from the world of work, organizations or education). Meanwhile, external factors are location (location/distance of BAZNAS which is quite far from where one lives), socialization (lack of socialization from BAZNAS institutions) and society. These three factors greatly influence the rarity or awareness of society to pay agricultural zakat